Aplicação da Tecnology Readiness Index para definição de escopo em projetos de automação - CASTRO, Marcia Inocencio de (2009)
The study of behavior adoption products and services - based technology by the consumer is as a great helper choices for design projects and in targeting market, represented a challenge for new products and technological services therefore means intensive growth of these products, various studies indicate also the frustration of consumers interact with technology acquired. Such evidence are particularly important as consumer beliefs are positively related to your acceptance or resistance in adopt products and technological services. In this context, the readiness to technology emerges as construct fundamental to understanding attitudes on consumer technology. This work is the general objective to propose a method to help engineers electricians in the design project automation home (AR) based on user profile technology from the analysis of personal characteristics, rather evaluating the propensity of individuals with adopt products and technological services air from drivers and inhibitors mental related optimism, inovatividade, discomfort and insecurity. We use as method technology readiness index (TRIx). With this, this work is useful in engineering project air, leading to a design of a project as close as possible claim preference and characteristic of the user / customer is aimed at greater satisfaction and quality products and solutions offered by AR